On the taxonomy of “Tigrioides” leucanioides (Walker) with descriptions of two new genera and ten new species from the Oriental realm (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2023)
The generic placement and the taxonomic structure of the complex traditionally identified in the collections as “Tigrioides” leucanioides (Walker, 1862) are revised. Two new genera and ten new species are described: Leucanithosia gen. n., Leucanithosia diehli sp. n. (Indonesia: northern Sumatra Island), Leucanithosia paraliaka sp. n. (Indonesia: northern Sumatra Island), Leucanithosia nansabon sp. n. (northern Myanmar), Leucanithosia witti sp. n. (Thailand, Laos, Southwest China (Yunnan) and Northeast India), Leucanithosia leptivalva sp. n. (the Philippines: Palawan Island), Leucanithosia inusitata sp. n. (Indonesia: northern Sumatra Island), Leucanithosia lampunga sp. n. (Indonesia: southern Sumatra Island), Philippinithosia gen. n., Philippinithosia lourensi sp. n. (the Philippines: Luzon, Negros and Mindoro Islands), Philippinithosia settelei sp. n. (the Philippines: Mindanao Island), and Philippinithosia reducta sp. n. (the Philippines: Mindanao, Leyte and Samar Islands). A new combination is established: Leucanithosia leucanioides (Walker, 1862), comb. n. The lectotype is designated for Lithosia leucanioides Walker, 1862. Adults, male and female genitalia are illustrated.